Repeated divergence of amphibians and reptiles across an elevational gradient in northern Madagascar. Issue 3 (16th March 2023) - Scherz, Mark D.; Schmidt, Robin; Brown, Jason L.; Glos, Julian; Lattenkamp, Ella Z.; Rakotomalala, Zafimahery; Rakotoarison, Andolalao; Rakotonindrina, Ricky T.; Randriamalala, Onja; Raselimanana, Achille P.; Rasolonjatovo, Safidy M.; Ratsoavina, Fanomezana M.; et al.
Abstract: How environmental factors shape patterns of biotic diversity in tropical ecosystems is an active field of research, but studies examining the possibility of ecological speciation in terrestrial tropical ecosystems are scarce. We use the isolated rainforest herpetofauna on the Montagne d'Ambre (Amber Mountain) massif in northern Madagascar as a model to explore elevational divergence at the level of populations and communities. Based on intensive sampling and DNA barcoding of amphibians and reptiles along a transect ranging from ca. 470–1470 m above sea level (a.s.l.), we assessed a main peak in species richness at an elevation of ca. 1000 m a.s.l. with 41 species. The proportion of local endemics was highest (about 1/3) at elevations >1100 m a.s.l. Two species of chameleons ( Brookesia tuberculata, Calumma linotum ) and two species of frogs ( Mantidactylus bellyi, M. ambony ) studied in depth by newly developed microsatellite markers showed genetic divergence up the slope of the mountain, some quite strong, others very weak, but in each case with genetic breaks between 1100 and 1270 m a.s.l. Genetic clusters were found in transect sections significantly differing in bioclimate and herpetological community composition. A decrease in body size was detected in several species with increasing elevation. The studied rainforest amphibians and reptiles show concordant population genetic differentiation across elevation along with morphological and niche differentiation. Whether this parapatric or microallopatric differentiation will suffice for the completion of speciation is, however, unclear, and available phylogeographic evidence rather suggests that a complex interplay between ecological and allopatric divergence processes is involved in generating the extraordinary species diversity of Madagascar's biota. Our study reveals concordant patterns of diversification among main elevational bands, but suggests that these adaptational processes are only part of the complex of processes leading to species formation, among which geographical isolation is probably also important. Abstract : We use the isolated rainforest herpetofauna on the volcanic Montagne d'Ambre (Amber Mountain) massif in northern Madagascar as a model to explore elevational divergence at the level of populations and communities. Based on intensive sampling and DNA barcoding of amphibians and reptiles along an elevational transect, we assessed a main peak in species richness at an elevation of ca. 1000 m a.s.l. with 41 species, and genetic divergences in four target species with turnover occurring between 1100 and 1270 m above sea level. Our data illustrate that species of rainforest amphibians and reptiles in Madagascar show concordant population genetic differentiation across elevation, along with morphological and elevational differentiation, and in partial agreement with patterns of community turnover.